2017
DOI: 10.1007/s41465-017-0038-z
|View full text |Cite
|
Sign up to set email alerts
|

Stroboscopic Visual Training: a Pilot Study with Three Elite Youth Football Goalkeepers

Abstract: ). The present pilot study is novel in SVT research in its inclusion of qualitative data collection methods and its use of participants. Three elite, youth football goalkeepers (EG) took part in a 7-week SVT programme, and their performance on 10 measures of visual and perceptual skills was compared with three matched control participants (CG). Individual, semistructured interviews were also conducted with the EG participants prior to the post-test. In general, there were no differences in the changes from pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 19 publications
3
42
0
1
Order By: Relevance
“…Existing research using SVT has demonstrated an improvement in visual response [30]; visual cognition [20]; and performance anticipatory timing [19]. In the later study, participants performed a simple timing prediction task using a basin anticipation timer, and the SVT group was found to improve accuracy and more consistent timing estimates immediately after training, and 10 min later.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Existing research using SVT has demonstrated an improvement in visual response [30]; visual cognition [20]; and performance anticipatory timing [19]. In the later study, participants performed a simple timing prediction task using a basin anticipation timer, and the SVT group was found to improve accuracy and more consistent timing estimates immediately after training, and 10 min later.…”
Section: Discussionmentioning
confidence: 83%
“…Recent research has investigated the use of SVT to improve sporting performance [2,[18][19][20][25][26][27][28][29][30][31][32]. Overall, these studies have utilised differing training period lengths and time points for measurements of performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If such training is done adequately, assessments [2,46] show that improvements may occur in nine tested abilities of students and stamina of the visual system. Positive results also appeared for toss-to-wall [46], baseball [2,13,47,48], basketball [49,50], cricket, football [9,51,52], fencing, frisbee [9], hockey [15,53], rugby [54], softball [55,56], tennis, table tennis [57], volleyball [49], and water-polo [49]. Outside of sports, improvements are known for motion sickness [58], older adults [59], and visually impaired youth [60].…”
Section: Methodsmentioning
confidence: 99%
“…Dispositivo footbonaut y Helix los cuales son dispositivos específicos para el trabajo de visión periférica, precisión y agilidad mental en futbolistas (23)(24)(25)(26). Dispositivos de entrenamiento visual Impulse Strobe Glasses, Nike SPARQ Vapor Strobe Eyewear, I-ON Training Glasses, Eyeport, Dynavision D2 los cuales aumentan la capacidad cognitiva para la captación de estímulos visuales mejorando la velocidad de procesamiento entre la información visual y su reacción en campo de juego (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Dispositivos Octopus Trainer y fitLight Trainer™ los cuales enfocan su trabajo en el entrenamiento de la velocidad de reacción y percepción visual aumentando la retroalimentación en campo de juego utilizando diferentes tipos de estímulos visuales (9,(38)(39)(40).…”
Section: Dispositivos Tecnológicos De Entrenamiento Cognitivounclassified